On the Simplex Algorithm Initializing - Nebojša V. Stojković; Predrag S. Stanimirović; Marko D. Petković; Danka S. Milojković (Abstract and Applied Analysis)
This paper discusses the importance of starting point in the simplex algorithm. Three different methods for finding a basic feasible solution are compared throughout performed numerical test examples. We show that our two methods on the Netlib test problems have better performances than the classical algorithm for finding initial solution. The comparison of the introduced optimization softwares is based on the number of iterative steps and on the required CPU time. It is pointed out that on average it takes more iterations to determine the starting point than the number of iterations required by the simplex algorithm to find the optimal solution.